Medical education in Malaysia: the evolving curriculum (Part 2) / Rokiah Ismail. - Ismail, Rokiah (Universiti Teknologi MARA Cawangan Selangor, 2017)
In Part 1, we took us through the path of the early implementation of the traditional medical curriculum. Although it worked in the early stages of medical education in Malaysia, it was deemed necessary to continually evaluate the curriculum to ensure that it meets the needs of national development and to keep pace with global trends. What were the triggers that initiated the global trend of curricular change in the 1970’s?